The Influence of the Hands-On Activity Learning Model Assisted by Scrapbook Media on the Learning Interest and Fiction Writing Ability of 5th Grade Students - Rahmi, Rahmi; Sulfasyah, Sulfasyah; Akhir, Muhammad (Edumaspul: Jurnal Pendidikan, 2024)
Writing fiction stories can develop students’ imagination, creativity and understanding of language and narrative structure. This research aims to examine the influence of the hands-on activity learning model assisted by scrapbook media on the interest in learning and ability to write fiction stories of class V Gugus II students, Patallassang District, Gowa Regency. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of 62 students who were divided into two groups, namely the experimental group which used the hands-on activity learning model assisted by scrapbook media and the control group which used the conventional learning model. Research instruments include a learning interest questionnaire and a fiction story writing ability test. The data obtained were analyzed using descriptive and inferential statistical techniques. The research results showed that there was a significant increase in interest in learning and ability to write fiction stories in the experimental group students compared to the control group. Multivariate Significance Test with a significant value of 0.000 < 0.05, which means that Ho is rejected. H1 is accepted, namely that there is an influence of the hands on activity model assisted by Scrapbook media simultaneously on the interest and ability to write fiction stories of class V students. The conclusion of this research is that the learning model Hands-on activities assisted by scrapbook media are effective in increasing fifth grade students’ interest in learning and ability to write fiction stories. The implication of this research is the need for teachers to adopt and integrate creative media such as scrapbooks in the learning process in order to improve the quality of education